Hyaluronic Acid-Based Injective Medical Devices: In Vitro Characterization of Novel Formulations Containing Biofermentative Unsulfated Chondroitin or Extractive Sulfated One with Cyclodextrins - Valentina Vassallo; Celeste Di Meo; Giuseppe Toro; Alberto Alfano; Giovanni Iolascon; Chiara Schiraldi (Pharmaceuticals, 2023)
Currently, chondroitin sulfate (CS) and hyaluronic acid (HA) pharma-grade forms are used for osteoarthritis (OA) management, CS as an oral formulations component, and HA as intra-articular injective medical devices. Recently, unsulfated chondroitin, obtained through biofermentative (BC) manufacturing, has been proposed for thermally stabilized injective preparation with HA. This study aimed to highlight the specific properties of two commercial injective medical devices, one based on HA/BC complexes and the other containing HA, extractive CS, and cyclodextrins, in order to provide valuable information for joint disease treatments. Their biophysical and biomechanical features were assayed; in addition, biological tests were performed on human pathological chondrocytes. Rheological measurements displayed similar behavior, with a slightly higher G′ for HA/BC, which also proved superior stability to the hyaluronidase attack. Both samples reduced the expression of specific OA-related biomarkers such as NF-kB, interleukin 6 (IL-6), and metalloprotease-13 (MMP-13). Moreover, HA/BC better ensured chondrocyte phenotype maintenance by up-regulating collagen type 2A1 (COLII) and aggrecan (AGN). Notwithstanding, the similarity of biomolecule components, the manufacturing process, raw materials characteristics, and specific concentration resulted in affecting the biomechanical and, more interestingly, the biochemical properties, suggesting potential better performances of HA/BC in joint disease treatment.